2016
DOI: 10.20944/preprints201612.0041.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential Enhanced Survivorship of Crown of Thorns Starfish Larvae due to Near-Annual Nutrient Enrichment during Secondary Outbreaks on the Central Mid-Shelf of the Great Barrier Reef, Australia

Abstract: The Great Barrier Reef (GBR) is currently experiencing widespread crown of thorns starfish (CoTS) outbreaks as part of the fourth wave of outbreaks since 1962. It is believed that outbreaks have become more frequent on the GBR and elsewhere in the Indo-Pacific associated with anthropogenic causes. The two widely accepted potential causes are (1) anthropogenic nutrient enrichment leading to increased biomass of phytoplankton, the food of the planktonic stage of larval CoTS; and (2) overfishing of predators on t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The CoTs affected sites in Abaiang disproportionately, and we are unable to account for the different severities of the outbreak across atolls. While larvae may have reached Tarawa at the same time as Abaiang, they may not have been as successful at settling and/or reaching maturity in Tarawa, but it is unlikely that this differential survivorship would be due to excess nutrients in Tarawa; on the Great Barrier Reef, researchers have found that CoTs outbreaks are positively correlated with high levels of nutrients [85,86]. CoTs will actively avoid feeding on P. rus in favor of other corals, but they will feed on less-preferred prey when their preferred food items are scarce [7,67,87].…”
Section: Cots Outbreakmentioning
confidence: 99%
“…The CoTs affected sites in Abaiang disproportionately, and we are unable to account for the different severities of the outbreak across atolls. While larvae may have reached Tarawa at the same time as Abaiang, they may not have been as successful at settling and/or reaching maturity in Tarawa, but it is unlikely that this differential survivorship would be due to excess nutrients in Tarawa; on the Great Barrier Reef, researchers have found that CoTs outbreaks are positively correlated with high levels of nutrients [85,86]. CoTs will actively avoid feeding on P. rus in favor of other corals, but they will feed on less-preferred prey when their preferred food items are scarce [7,67,87].…”
Section: Cots Outbreakmentioning
confidence: 99%
“…The higher densities of Coralliophila violacea observed at sites with more N loading may also play an important role in impacting massive Porites colonies at the reef scale. Land‐based pollution increases phytoplankton populations that often promote invertebrate larval success (Brodie et al., 2017; Fabricius et al., 2010; Sutcliffe Jr, 1973), which might, in turn, promote higher muricid gastropod population densities on coral reefs with higher nutrient loading (Li et al., 2013; Moyer et al., 1982). Populations of corallivorous snails can increase after sites are perturbed by land‐based pollution, resulting in higher snail densities on live coral colonies (Li et al., 2013; Moyer et al., 1982).…”
Section: Discussionmentioning
confidence: 99%
“…On southern offshore reefs, high Chl a is the result of recurrent intrusions of nutrient-rich waters by upwelling on the shelf break (e.g., Andrews and Furnas 1986, Berkelmans et al 2010), and it has been hypothesized that primary outbreaks could emerge there with no relation to river-flood events (Moran et al 1988, Johnson 1992, Miller et al 2015). Although the causes of primary outbreaks on the GBR are yet to be resolved (Pratchett et al 2014, 2017), the present model can be used to explore the timing and mechanisms of the propagation of secondary outbreaks facilitated by nutrient availability (Brodie et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The CoTS spawning period on the GBR extends from December to February (Babcock and Mundy 1992, Brodie et al 2017). CoTS fecundity expressed as number of eggs is a function of wet weight (Kettle and Lucas 1987) derived from the representative mean size (diameter) of each age class of CoTS.…”
Section: Methodsmentioning
confidence: 99%